Exploring an intervention on how to integrate local or indigenous knowledge on the features of the moon in Grade 4 classes - Magwentshu, Thando (Rhodes University, Faculty of Education, Department of Education, 2020)
The National Curriculum Statement (R-12) calls on all Natural Sciences teachers to integrate local or indigenous knowledge (IK) into their lessons. However, this seems to be easier said than done. For instance, in my experience as a Natural Sciences teacher I have observed that the Department of Education does not adequately equip and support teachers with the necessary pedagogical skills to integrate IK in science lessons. It is against this background that this study sought to explore an intervention on the development and implementation of model lessons on features of the moon that integrate local or IK in Grade 4 classes. The study adopted a qualitative case study approach underpinned by an interpretivist perspective. Within the interpretive paradigm, a qualitative case study approach was employed. The participants were four Grade 4 Natural Sciences and Technology teachers from selected schools in the Chris Hani West District. Data were gathered and triangulated using questionnaires, semi-structured interviews, document analysis, a presentation by an expert community member, workshop discussions and journal reflections. Vygotsky's socio-cultural theory and Shulman's pedagogical content knowledge (PCK) were used as a theoretical framework and analytical framework respectively. From the socio-cultural theory, three concepts were used: social interactions, mediation of learning and the zone of proximal development (ZPD). Additionally, within PCK, Mavhunga and Rollnick's (2013) five Topic Specific Pedagogical Content Knowledge components: learners' prior knowledge, what is difficult to understand, curricular saliency, representations and conceptual teaching strategies were used as analytical tools. A thematic approach to qualitative data analysis was adopted, to come up with sub-themes in relation to my research questions. The findings from this study revealed that before the intervention, some teachers had a narrow understanding of local or IK and how it could be integrated in their lessons. As a result, some teachers had never implemented integration of local or IK as required by the Curriculum and Assessment Policy Statement (CAPS) and the principles of the National Curriculum Statement. The findings of this study thus showed that after the intervention, teachers felt equipped with understanding of local or IK. Additionally, they were able to develop their own model lessons that integrated it. The study thus recommends that teachers should be supported as far as possible in order to be able to integrate local or IK in their science lessons.
Keywords: Moon -- Study and teaching (Elementary) -- South Africa; Science -- Study and teaching (Elementary) -- South Africa; Education, Elementary -- South Africa; Ethnoscience -- Study and teaching (Elementary) -- South Africa